ROOT CAUSE ANALYSIS DARI INKONSISTENSI PEMELIHARAAN PERALATAN MEDIS DI RUMAH SAKIT “X” - Arifin, M Syamsul (Jurnal Administrasi Publik, 2024)
Root Cause Analysis of Inconsistencies in  Medical Equipment Maintenance at Hospital 'X'. The purpose of this study is to identify the variables responsible for the lack of consistency in the maintenance of medical equipment at "X" hospital. This study use a descriptive qualitative approach. Interviews and focus groups provided primary data. Secondary data came from document studies, observations, and literature reading. Data was collected on September–October 2023. The root causes examined in fishbone diagrams encompass human elements, methodologies, machinery, materials, and financial aspects. Hospitals must formulate a strategic program of action to solve these challenges.